Digital Literacy and Students' Reading Interest in the Implementation of the Merdeka Curriculum - Annisa Rahma; Hildawati Hildawati; Andi Anirah; Allifia Sri Cahyani (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
The development of digital technology encourages schools to adjust their learning strategies, including enhancing students' digital literacy and reading interest. This study aims to analyze the implementation of digital literacy and its relation to students' reading interest in the context of the Merdeka Curriculum at SMA Bina Insan Palu. The research employed a qualitative approach with a case study design, collecting data through observation, interviews with teachers and students, and documentation of learning activities. The findings indicate that students' digital literacy levels fall into a fairly good category, yet they still require specific guidance in aspects such as source verification, proper citation, and understanding of digital ethics. Reading interest tends to increase when students are provided with interactive digital reading materials, Pancasila Student Profile (P5) projects, and authentic assessments in the form of reflections or short reviews. The main challenges faced include limited access to devices, fluctuating network quality, and a lack of curated reading materials suitable for students' proficiency levels. The discussion highlights that interventions such as tiered digital reading curation, daily reading routines, authentic assessments, and technical support (devices and internet connections) are practical strategies to improve both digital literacy and students' reading interest. The study concludes that the success of the Merdeka Curriculum implementation at SMA Bina Insan Palu is strongly determined by teachers' readiness, institutional support, and the provision of adequate digital infrastructure